Biochar production from freshwater algae by slow pyrolysis - Chaiwong K. (2017)
A study on the feasibility of biochar production from 3 kinds of freshwater algae, viz. Spirulina, Spirogyra and Cladophora, was undertaken. Using a slow pyrolysis process in a specially designed reactor, biochar could be generated at 550oC under nitrogen atmosphere. The yields of biochar were between 28-31% of the dry algae © 2012 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.